Peptoniphilus duodeni sp. nov., a new bacterial species identified in human duodenum. (March 2017) - Mailhe, Morgane; Ricaboni, Davide; Vitton, Véronique; Cadoret, Frédéric; Fournier, Pierre-Edouard; Raoult, Didier
Abstract: We present here the main characteristics of Peptoniphilus duodeni strain Marseille-P2932 (= CSUR P2932, = DSM 103346) that was isolated from the duodenum of a 60-year-old male.